Thermal effect of a fire on a steel beam with corrugated wall with fireproof mineral-wool cladding - Nekora, Valeriia; Sidnei, Stanislav; Shnal, Taras; Nekora, Olga; Lavrinenko, Ludmila; Pozdieiev, Serhii (Eastern-European Journal of Enterprise Technologies, 2021)
This paper reports a study into the possibility of applying a simplified approach, recommended by standards for conventional steel beams, to determine the heating temperature under the conditions of a fire in relation to steel I-beams with a corrugated wall. The research is predetermined by the limitation of methods that make it possible to determine the heating temperature of this type of beam in a fire using engineering methods with a small amount of calculations. Technical data on steel beams with cladding have been considered for calculation, the features of heat impact of fire on them have been analyzed, a calculation procedure has been devised, the estimation schemes have been built, and the calculations have been performed. Data on the temperature distribution in the cross-sections of beams with and without cladding were obtained by using a simplified method recommended by standards and the refined method based on a finite-element method. Mathematical models have been constructed for calculations that describe the effect of a standard temperature regime of fire on the distribution of temperature in each minute in the cross-sections of steel beams with and without cladding. The models have been described on the basis of the differential equation of thermal conductivity, boundary conditions of the third kind, which take into consideration convective and radiant heat transfer. It was established that the mineral wool cladding of the beam with a corrugated wall is a reliable fire protection agent. The heating temperature of the beam does not reach a critical value of 500 °C in 60 minutes, which provides the class of this beam with the most stringent requirements for its fire resistance in accordance with the classification in line with the acting norms in Ukraine. The simplified method, recommended by the current standards of the European Union and Ukraine, could be effectively used to analyze the fire resistance of these beams and is the basis of the procedure for the estimated assessment of the fire resistance of these structures